The Professional's Guide to Fair Value : the Future of Financial Reporting - Catty, James P. (Hoboken : John Wiley & Sons, 2012)
An all-encompassing guide to the elements and basics of fair valueWith the important role fair value is playing in the creation of a converged set of global accounting standards, demand for products in this category is growing spectacularly. The elements and basics of fair value are covered, including risk, dealing with the SEC, and details on legal responsibility. In addition, sample financial statements are included, along with tables, recommended applicable techniques, and management checklists for those who are responsible for preparing and approving of financial statements. Written by the.
Stage 2: Establish the Consideration's Fair ValueKnowledge of the Industry; Stage 3: Identify All the Items Involved; Stage 4: Select Appropriate Valuation Techniques; Stage 5: Estimate Fair Values and Reconcile Rates of Return; Conclusion; Chapter 14: Impairment; Reporting Units; Cash-Generating Units; Goodwill; Allocations; GAAP Long-Lived Assets Impairment Test; IFRS Impairment Test; GAAP Goodwill Impairment Test; Chapter 15: The Auditor's Blessing; Auditing Fair Values; Conclusion; About the Author; Index.
Print version record.
Keywords: Fair value -- Accounting -- Standards; Financial statements; BUSINESS & ECONOMICS -- Accounting -- General; Business; BUSINESS & ECONOMICS -- Accounting -- Financial; Business; Electronic books